Delay Maturation in Occipital Lobe in Girls With Inattention Subtype of Attention-Deficit Hyperactivity Disorder. (September 2020) - Chang, Tung-Ming; Yang, Rei-Cheng; Chiang, Ching-Tai; Ouyang, Chen-Sen; Wu, Rong-Ching; Yu, Sebastian; Lin, Lung-Chang
Attention-deficit hyperactivity disorder (ADHD) is a common childhood neuropsychiatric disorder. Differences in the presentations of ADHD between boys and girls have been well established. Three subtypes of ADHD exist. In addition to sex difference, different mechanisms may underlie different subtypes. The present study enrolled 30 girls with the inattentive subtype of ADHD and 30 age-matched controls. Low-resolution electromagnetic tomography (LORETA) and instantaneous frequency were used to analyze electroencephalography (EEG) for investigating the brain area and EEG bands involved in girls with inattentive ADHD. We found that the instantaneous frequencies in all EEG channels in girls with ADHD were lower than those in controls. Alpha 2 was the only EEG band that showed significant difference in current density between the ADHD and control groups ( P = .0014). In the entire brain area, the posterior cingulate cortex, cingulate gyrus, and precuneus demonstrated the most significant difference between the ADHD and control groups. Our results suggest that brain maturation delay in the posterior areas might result in the inattention subtype of ADHD. In addition, posterior cingulate cortex, cingulate gyrus, and precuneus may play a critical role in the pathogenesis of ADHD. Our study provides a new approach method and possible mechanism of girls with inattentive subtype ADHD.